2016
DOI: 10.1021/acsami.6b09377
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between Antibiotics and Graphene-Based Materials in Water: A Comparative Experimental and Theoretical Investigation

Abstract: Complex interactions between antibiotics and graphene-based materials determine both the adsorption performance of graphene-based materials and the transport behaviors of antibiotics in water. In this work, such interactions were investigated through adsorption experiments, instrumental analyses and theoretical DFT calculations. Three typical antibiotics (norfloxacin (NOR), sulfadiazine (SDZ) and tetracycline (TC)) and different graphene-based materials (divided into two groups: graphene oxides-based ones (GOs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 98 publications
(33 citation statements)
references
References 40 publications
2
29
0
2
Order By: Relevance
“…As a matter of a fact, on the experimental framework it has been shown that GO platelets can act as an effective medium for the transportation of aromatic environmental pollutants and elimination of organic matter and antibiotics in water solutions. Graphene‐based carriers have also emerged as optimal candidates in therapeutics delivery: they have served for the transportation of water soluble and insoluble drugs as well as for nucleic acids loading .…”
Section: Introductionmentioning
confidence: 99%
“…As a matter of a fact, on the experimental framework it has been shown that GO platelets can act as an effective medium for the transportation of aromatic environmental pollutants and elimination of organic matter and antibiotics in water solutions. Graphene‐based carriers have also emerged as optimal candidates in therapeutics delivery: they have served for the transportation of water soluble and insoluble drugs as well as for nucleic acids loading .…”
Section: Introductionmentioning
confidence: 99%
“…In the aqueous solution, TC has three ionization equilibrium constants, i.e. pK a1 = 3.30, pK a2 = 7.68, and pK a3 = 9.68 . Therefore, at different pH values, TC can be dissolved into four different forms, including the positive ion form (TC + ), amphoteric ion (TC ± ), negative ion form (TC − ), and dianion form (TC 2− ).…”
Section: Resultsmentioning
confidence: 99%
“…pK a1 = 3.30, pK a2 = 7.68, and pK a3 = 9.68. 43 Therefore, at different pH values, TC can be dissolved into four different forms, including the positive ion form (TC + ), amphoteric ion (TC ± ), negative ion form (TC − ), and dianion form (TC 2− ). With a low initial pH, TC would lose all its electrons, thus appearing in the form of TC + .…”
Section: Effect Of Ph On Adsorption Performancementioning
confidence: 99%
“…Mesoporous materials are used as adsorbents because of their high surface area and versatile surface functional groups, which have attracted increasing attention [10,11]. Reduced graphene oxide (rGO), a derivative of graphene, shows great promise as an effective adsorbent because of its large specific surface area and abundant pore structures [12,13]. During the past few years, many studies have been carried out to investigate the removal of heavy metal ions and dyes using rGO and very promising results have been achieved.…”
Section: Introductionmentioning
confidence: 99%